Informed Cytology for Triaging HPV-Positive Women: Substudy Nested in the NTCC Randomized Controlled Trial. (7th January 2015) - Bergeron, Christine; Giorgi-Rossi, Paolo; Cas, Frederic; Schiboni, Maria Luisa; Ghiringhello, Bruno; Dalla Palma, Paolo; Minucci, Daria; Rosso, Stefano; Zorzi, Manuel; Naldoni, Carlo; Segnan, Nereo; Confortini, Massimo; et al.
Abstract : Background: Human papillomavirus (HPV)–based screening needs triage. In most randomized controlled trials (RCTs) on HPV testing with cytological triage, cytology interpretation has been blind to HPV status. Methods: Women age 25 to 60 years enrolled in the New Technology in Cervical Cancer (NTCC) RCT comparing HPV testing with cytology were referred to colposcopy if HPV positive and, if no cervical intraepithelial neoplasia (CIN) was detected, followed up until HPV negativity. Cytological slides taken at the first colposcopy were retrieved and independently interpreted by an external laboratory, which was only aware of patients' HPV positivity. Sensitivity, specificity, and positive (PPV) and negative (NPV) predictive values were computed for histologically proven CIN2+ with HPV status–informed cytology for women with a determination of atypical squamous cells of undetermined significance (ASCUS) or more severe. All statistical tests were two-sided. Results: Among HPV-positive women, informed cytology had cross-sectional sensitivity, specificity, PPV and 1-NPV for CIN2+ of 85.6% (95% confidence interval [CI] = 76.6 to 92.1), 65.9% (95% CI = 63.1 to 68.6), 16.2% (95% CI = 13.0 to 19.8), and 1.7 (95% CI = 0.9 to 2.8), respectively. Cytology was also associated with subsequent risk of newly diagnosed CIN2+ and CIN3+. The cross-sectional relative sensitivity for CIN2+ vs blind cytology obtained by referring to colposcopy and following up only HPV positive women who had HPV status–informed cytology greater than or equal to ASCUS was 1.58 (95% CI = 1.22 to 2.01), while the corresponding relative referral to colposcopy was 0.95 (95% CI = 0.86 to 1.04). Conclusions: Cytology informed of HPV positivity is more sensitive than blind cytology and could allow longer intervals before retesting HPV-positive, cytology-negative women.